1975
DOI: 10.1007/bf02120764
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cultivation of cells from the chorioallantoic membrane of chick embryos

Abstract: By treatment of chorioallantoic membranes from embryonated eggs with collagenase and hyaluronidase before the conventional application of trypsin cells could be grown in culture which supported growth of a large variety of myxoviruses, herpesviruses, avian reoviruses and the infectious bronchitis virus of chickens. The cultures could be used for sensitive plaque assays and neutralization tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Tissue Cultures Primary chick embryo fibroblasts and chorioallantoic membrane (CAM) cells were prepared as described (2,13). The preparation of the CAM tissue cultures was modified as follows: the concentration of EDTA should be 0.02 per cent, and we used 80 mg collagenase and 10 mg hyaluronidase in 500 ml of GKN for the treatment of 30 to 40 CAM membranes from embryonated eggs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue Cultures Primary chick embryo fibroblasts and chorioallantoic membrane (CAM) cells were prepared as described (2,13). The preparation of the CAM tissue cultures was modified as follows: the concentration of EDTA should be 0.02 per cent, and we used 80 mg collagenase and 10 mg hyaluronidase in 500 ml of GKN for the treatment of 30 to 40 CAM membranes from embryonated eggs.…”
Section: Methodsmentioning
confidence: 99%
“…NAGAI et al (9) reported t h a t chorioallantoic membrane (CAS{) cells (2) in vitro are permissive for apathogenic as well as pathogenic strains of NDV. I n this s t u d y we have found the CAM cells to be permissive for p a r a m y x o v i r u s Yucaipa (PMY) and Sendal, virus.…”
Section: Introductionmentioning
confidence: 99%
“…CV-1 cells (TC7 clone) were grown in Eagle's medium with 10% fetal calf serum, and HeLa cells were grown in reinforced Eagle's medium with 5% fetal calf serum as described (1) (Eagle's medium contains 5.5 mM glucose and the reinforced medium contains 22 mM glucose). Primary chicken embryo fibroblasts (CEFs) and chorioallantoic membrane cells were prepared as described (8,9) …”
Section: Abstacmentioning
confidence: 99%
“…For metabolic labeling NDV was grown in primary chick embryo or in cultured cells of the chorioallantoic membrane (CAM) (Cursiefen and Becht, 1975).…”
Section: Introductionmentioning
confidence: 99%